Last flag flying [videorecording (DVD)] - Linklater, Richard, 1960-; Carell, Steve, 1962-; Cranston, Bryan, 1956-; Fishburne, Laurence, III, 1961-; Tyson, Cicely; Ponicsan, Darryl (Lions Gate Entertainment, 2018)
Thirty years after they served together in Vietnam, a former Navy Corpsman Larry "Doc" Shepherd re-unites with his old buddies, former Marines Sal Nealon and Reverend Richard Mueller, to bury his son, a young Marine killed in the Iraq War.